Analysis Of Entrepreneurial Literacy of Students in SMK Negeri 5 Makassar - Muhammad Jufri; Agus Syam; Sudarni Sudarni; Asmayanti Asmayanti (Universitas Negeri Makassar, 2021)
This study aims to analyze the entrepreneurial literacy of the students of SMK Negeri 5 Makassar. This research is categorized as a quantitative descriptive study with a sample of 35 students. The data obtained through the distribution of questionnaires with a Likert scale. The analytical technique used is descriptive analysis. The results of the study show that entrepreneurial literacy has an important role in increasing interest in entrepreneurship. This study shows that entrepreneurial literacy has a positive and significant effect on entrepreneurial interest in SMK Negeri 5 Makassar students.